Spatial attention enhances network, cellular and subthreshold responses in mouse visual cortex - Anderson Speed (Nature Portfolio, 2020)
Extensive research in primates shows that attention to space improves behavioural performance as well as neural responses to stimuli in that location. Here, the authors establish a visual spatial attention task in mice and report on attentional modulation of behaviour, as well as neural correlates from subthreshold responses in single cells to spikes and LFP at network level.